Maintenance plan proposal for a turning machine from machining laboratory of Brasília University - Santiago, Letícia Corrêa Bastianon; Nunes, Bruno Souza; Amaral, Ian Rocca; Conceição, Márcio da Silva; Santos, Aline Gonçalves dos; Oliveira, Déborah de (Brazilian Journal of Production Engineering, 2022)
Public universities contribute most of the research developed in Brazil, mainly from studies based on equipment available in the laboratories of the respective universities. In many cases, these equipments are kept operational for long periods through proper maintenance operations. With a focus on the machining area, this fact becomes even more relevant since the equipment is very robust and durable. From a bibliometric review, it was possible to verify that almost 50% of the studies developed in turning in Brazil uses equipment with more than 20 years. Thus, this study aims to develop a maintenance plan for the lathes (turning machines) available at the Machining Laboratory of the University of Brasília. For this, initially the most suitable type of maintenance was identified, followed by the determination of the verification components. After this step, verification activities, implementation and control plans were selected. Through the mentioned steps, it was identified that preventive maintenance, associated with the tools used, stands out for the conservation of lathes. In addition, this maintenance plan aims to contribute to other teaching and research laboratories and can be replicated for use on other machines.